Hubungan antara Keterampilan Evaluasi dengan Keterlaksanaan Evaluasi Program BK di SMA Se-Kecamatan Cilinci Jakarta Utara - Khairunisa Khairunisa; Ariyana Rustam; Ihsan Nurkholis; Anaway Irianti Mansyur; Maslikhah Maslikhah; Aip Badrujaman (JKI (Jurnal Konseling Indonesia), 2019)
This study aims to determine the relationship between evaluation skills and the implementation of a guidance and counseling program evaluation in Cilincing North Jakarta Sub-District High School. This research uses quantitative research using survey methods. The collection technique used in this study is a Guttman scale questionnaire and the data analysis technique used in this study is the Product Moment Correlation. This research was conducted in North Jakarta with the subjects of high school teachers in Cilincing Sub-District, North Jakarta City, 30 teachers were divided into 7 Public High Schools and 4 Private High Schools. The results of this study indicate the correlation coefficient between evaluation skills (X) with program evaluation exercise (Y) r_xy = 0.64> rtabel = 0.36, which means that there is a positive relationship between evaluation skills and the implementation of school guidance and counseling evaluation programs which means if the evaluation skills of the counselor are good, the better the evaluation of the guidance and counseling program at the school.